Rosuvastatin reduces neointima formation in a rat model of balloon injury - Preusch, Michael; Vanakaris, A.; Bea, Florian; Ieronimakis, N.; Shimizu, T.; Konstandin, Mathias; Morris-Rosenfeld, S.; Albrecht, C.; Kranzhöfer, A.; Katus, Hugo; Blessing, Erwin; Kranzhöfer, Roger (European journal of medical research, 2010)
Background: Processes of restenosis, following arterial injury, are complex involving different cell types producing various cytokines and enzymes. Among those enzymes, smooth muscle cell-derived matrix metalloproteinases (MMPs) are thought to take part in cell migration, degrading of extracellular matrix, and neointima formation. MMP-9, also known as gelatinase B, is expressed immediately after vascular injury and its expression and activity can be inhibited by statins. Using an established in vivo model of vascular injury, we investigated the effect of the HMG-CoA reductase inhibitor rosuvastatin on MMP-9 expression and neointima formation. Materials and methods: 14-week old male Sprague Dawley rats underwent balloon injury of the common carotid artery. Half of the animals received rosuvastatin (20 mg/kg body weight/day) via oral gavage, beginning 3 days prior to injury. Gelatinase activity and neointima formation were analyzed 3 days and 14 days after balloon injury, respectively. 14 days after vascular injury, proliferative activity was assessed by staining for Ki67. Results: After 14 days, animals in the rosuvastatin group showed a decrease in total neointima formation (0.194 ± 0.01 mm2 versus 0.124 ± 0.02 mm2, p < 0.05) as well as a reduced intima/media ratio (1.26 ± 0.1 versus 0.75 ± 0.09, p < 0.05). Balloon injury resulted in increased activity of MMP-9 3 days after intervention for both rosuvastatin treated animals and controls with no significant difference observed between the groups. There was a trend towards a reduction in the number of Ki67-positive cells 14 days after injury. Conclusions: Rosuvastatin attenuates neointima formation without affecting early MMP-9 activity in a rat model of vascular injury.
Gesehen am 08.05.2023